Heart Rate Variability and Direct Current Measurement Characteristics in Professional Mixed Martial Arts Athletes - Joseph O. C. Coyne; Aaron J. Coutts; Roman Fomin; Duncan N. French; Robert U. Newton; G. Gregory Haff (MDPI AG, 2020)
This study's purpose was to examine heart rate variability (HRV) and direct current potential (DC) measures' sensitivity and correlations between changes in the acute recovery and stress scale (ARSS) and the previous day's training load. Training load, HRV, DC and ARSS data were collected from fourteen professional mixed martial arts athletes (32.6 ± 5.3 years, 174.8 ± 8.8 cm, 79.2 ± 17.5 kg) the following morning after hard, easy and rest days. Sensitivity was expressed as a signal-to-noise ratio (SNR, inter-day typical error (TE) or coefficient of variation (%CV) divided by intra-day TE or %CV). Correlations between HRV, DC and ARSS with training load were also examined. The SNRs for the various HRV and DC measures were acceptable to good (1.02-2.85). There was a 23.1% CV average increase between measures taken between different locations versus the same location. Training load changes were not correlated with HRV/DC but were correlated with ARSS stress variables. Practitioners should be aware of HRV/DC variability; however the daily training signal was greater than the test-retest error in this investigation. Upon awakening, HRV/DC measures appear superior for standardization and planning. HRV and DC measures were less sensitive to the previous day's training load than ARSS measures.